ON THE ISSUE OF PROVISION OF GUARANTEES FOR EMPLOYEES ELECTED TO ELECTED POSITIONS - Kuksin, S. Yu. (Київський національний університет імені Тараса Шевченка, 2020)
Problem setting. The modern world is characterized by the rapid development of digitalization and the dynamic development of economic and labor relations. The emergence of new forms of employment, new professions and activities requires labor legislation to respond quickly and adapt to modern realities. However, the Labor Code of Ukraine (hereinafter - the Labor Code) in some institutions of labor law is in no hurry, not even trying to keep up with the new realities. Thus, Chapter VIII Guarantees and Compensation, which regulates mainly the issues of guarantee and compensation payments made for the benefit of employees, are regulated, as well as other issues related to the legislative provision of guarantees to employees, often becomes the subject of dissertation research and discussion and debate among scholars and practitioners.Of particular note is Article 118 of the Labor Code, which regulates guarantees for employees elected to elected positions. Because election is an essential feature of special legal regulation of labor relations of employees.The purpose of this article is to explore the features of the implementation of guarantees for employees elected to elected positions, to outline the problematic issues.Target of research. Research on the issues raised can be found in the works of S. Alekseev, O. Barabash, N. Bolotina, V. Venediktov, M. Vitruk, O. Protsevsky, V. Rotan, VM Skobelkina, R. Khalfina, O. Yaroshenko and others. However, we must state that there is no thorough research in the context of the guarantee of employees elected to elected positions.Article’s main body. The article considers the problematic issues of implementation of guarantees for employees elected to elected positions. Article 118 of the Labor Code of Ukraine is analyzed in view of the historical aspect. The author raises the issue of elected positions, in which organizations the guarantees of Article 118 apply. The problem of providing previous work (positions) to former civil servants who worked in elected positions in public authorities or local governments is highlighted. The characters of the status of a deputy of local councils and a People's Deputy in terms of providing previous work (position) are given. The constitutional representation on the raised topic is analyzed. It is noted that determining the procedure for reinstatement (appointment or election) to a previous judicial position of a citizen after the termination of the powers of a People's Deputy of Ukraine cannot be resolved by official interpretation of the Law of Ukraine «On the Status of People's Deputy».Conclusions. Thus, the issues raised by us regarding the peculiarities of the implementation of the provisions of Article 118 of the Labor Code give grounds to argue that the article has many shortcomings in the context of practical application. And this is largely due to the temporal effect of those laws with which Article 118 of the Labor Code must comply. And given the fact that they were all adopted much later, of course, we have in practice a different understanding of its implementation. Therefore, we see the expediency in a radical revision of the provisions of Article 118 of the Labor Code, in addition, we must understand that today's realities are significantly different from the time when this rule was adopted, so the question must be thoroughly investigated: whether there is a need for this rule.

У статті розглянуті проблемні питання реалізації гарантій для працівників, обраних на виборні посади. Проаналізована стаття 118 Кодексу законів про працю України з огляду на історичний аспект. Автором порушене питання на виборні посади, в яких саме організаціях діють гарантії статті 118. Висвітлено проблему надання попередньої роботи (посади) колишнім державним службовцям, які працювали на обраних посадах в органах державної влади чи місцевого самоврядування. Надана характери статусу депутата місцевих рад та народного депутата в частині надання попередньої роботи (посади). Проаналізовано конституційне подання щодо порушеної теми. Зроблений висновок, має бути ґрунтовно досліджене питання:чи існує взагалі потреба у положеннях статті 118 Кодексу законів про працю України.
ЩОДО ПИТАННЯ НАДАННЯ ГАРАНТІЙ ДЛЯ ПРАЦІВНИКІВ, ОБРАНИХ НА ВИБОРНІ ПОСАДИ
Keywords: Key words: elected positions; previous job; civil servant; guarantees; public organization; political party.; Ключові слова: виборні посади; попередня робота; державний службовець; гарантії; громадська організація; політична партія